The Influence of Parents’ Parenting and Emotional Quotient on Students’ Social Skills - Siti Masyithoh (TARBIYA: Journal of Education in Muslim Society, 2017)
Abstract This research aims at knowing and finding empirical data about the influence of independent variables, i.e., parenting and emotional quotient on students’ social skills as a dependent variable.This study employed a quantitative research design in the form of ex-post-facto or causal comparative with the 3x2 factorial design. The method used to collect the data was surveyed with a questionnaire. The data were analyzed by using two-way analysis of variance. The samples are 172 students of the elementary school in Mustika Jaya Bekasi. The result of this research showed that the social skills gained by the students with democratic parenting on average were highest among others. Further, the students having high emotional quotient showed better social skills compared to those with low emotional quotient. The students raised with democratic parenting both with high and low emotional quotient earned the highest social skills. Students with high emotional quotient nurtured by permissive parenting showed better social skills than those raised by authoritarian parenting. In contrast, students with low emotional quotient raised with authoritarian parenting produced better social skills than those nurtured by permissive parenting. So, there is the influence of parenting and emotional quotient on students’ social skills at 6th Grade of elementary schools in Mustika Jaya Bekasi District. Abstrak Penelitian ini bertujuan untuk mengetahui dan menemukan data empiris tentang pengaruh variabel bebas, yaitu pola asuh dan kecerdasan emosional terhadap ketrampilan sosial siswa sebagai variabel dependen. Penelitian ini menggunakan rancangan penelitian kuantitatif dalam bentuk kompresif faktual atau komparatif kausal dengan 3x2 desain faktorial. Metode yang digunakan untuk mengumpulkan data adalah survei dengan kuesioner. Data dianalisis dengan menggunakan analisis varian dua arah. Sampelnya adalah 172 siswa sekolah dasar di Mustika Jaya Bekasi. Hasil penelitian ini menunjukkan bahwa keterampilan sosial yang diperoleh siswa dengan pola asuh demokratik rata-rata paling tinggi. Selanjutnya, siswa yang memiliki kecerdasan emosional tinggi menunjukkan kemampuan sosial yang lebih baik dibandingkan dengan mereka yang memiliki kecerdasan emosional rendah. Para siswa yang diangkat dengan pola asuh demokratis baik dengan kecerdasan emosional tinggi maupun rendah memperoleh keterampilan sosial tertinggi. Siswa dengan kecerdasan emosional tinggi yang dipelihara dengan pola asuh permisif menunjukkan kemampuan sosial yang lebih baik daripada yang diangkat oleh pola asuh otoriter. Sebaliknya, siswa dengan kecerdasan emosional rendah yang diangkat dengan pola asuh otoriter menghasilkan keterampilan sosial yang lebih baik daripada yang dipelihara oleh pola asuh permisif. Jadi, ada pengaruh parenting dan emotional quotient terhadap keterampilan sosial siswa di kelas 6 SD di Mustika Jaya Kabupaten Bekasi.Kata kunci: orangtua orangtua, kecerdasan emosi, keterampilan sosial. How to Cite : Masyithoh, S. (2017). The Influence of Parents’ Parenting and Emotional Quotient on Students’ Social Skills. TARBIYA: Journal of Education in Muslim Society, 4(1), 32-44  doi:10.15408/tjems.v4i1.5901. Permalink/DOI: http://dx.doi.org/10.15408/tjems.v4i1.5901